Pengaruh Motivasi Kerja, Kompensasi dan Beban Kerja Terhadap Kinerja Karyawan PT. Sapadia Wisata Boombara Waterpark Rantauprapat - Ade Parlaungan Nasution (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of work motivation, compensation and workload on employee performance. This Type Of Research Is Associative Research. Data collection in this study was conducted through a survey approach with a type of quantitative descriptive research by distributing questionnaires to 30 respondents, while the population used in this study are employees of PT. Sapadia Tourism Boombara Waterpark Rantauprapat. Data collection techniques are carried out by interviews, questionnaires and documentation studies. Data analysis tools used in this study using SPSS (Statistical product Sofware Solution). Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and determination coefficient test (R2). The results of this study showed that partially work motivation affects the performance of employees at PT. Sapadia Tourism Boombara Waterpark Rantauprapat with the value of thitung (5.089) > ttable 1.708) and the significance level of 0.000 < 0.05. Partial compensation effect on employee performance at PT. Sapadia Tourism Boombara Waterpark Rantauprapat with the value of thitung (4.099) > ttable (1.708) and the significance level of 0.000<0.05. Partially workload effect on employee performance at PT. Sapadia Tourism Boombara Waterpark Rantauprapat with the value of thitung (5,892) > ttable (1,708) and the significance level of 0,000 < 0,05. In simultaneous testing (test F) it is known that simultaneously work motivation, compensation and workload have a positive and significant effect on employee performance at PT. Sapadia Wisata Boombara Waterpark Rantauprapat with the results showed that the value of Fhitung is (22.961) > Ftable (2.98) and the significance level of 0.00 < 0.05. Through testing the coefficient of determination of employee performance variables can be explained by work motivation, compensation and workload of 69.4%. While the remaining 30.6% influenced by other variables that are not studied in this study.